Efek Pemberian Tepung Limbah Tauge dalam Ransum Terhadap Bobot Telur dan Produksi Telur Puyuh (Cortunix-Cortunix Japonica) - Muhammad Jurhadi Kadir; Ahsan Ahsan; Irmayani Irmayani (Fakultas MIPA UNM, 2022)
Abstract. This study aims to determine the effect of giving bean sprouts with different levels in the ration on egg production and quail egg weight. Using a completely randomized design (CRD) with 4 treatment levels and 3 replications so that there were 12 units of observation, each experimental unit consisted of 10 quails with a total of 120 quails. Each treatment consisted of P0: ration without bean sprouts waste (control), P1: ration with 3% bean sprouts waste, P2: ration with 6% bean sprouts waste, P3: ration with 8% bean sprouts waste. The results of variance showed that the addition of bean sprouts at different levels had a significant effect (p≤0.05) on egg production and a very significant effect (p≤0.01) on quail egg weight. The average quail egg production ranged from 70.83% - 94.17%, while the average quail egg weight ranged from 11.73% - 12.64%. It was concluded that the provision of bean sprouts waste flour in quail rations with a concentration of 3% gave the best effect on egg production and quail egg weight (Coturnix-coturnix japonica). Keywords: bean sprout waste flour, egg production, egg weight, quail eggs